MRI appearances of ovarian serous borderline tumor: Pathological correlation. Issue 1 (28th August 2014) - Zhao, Shu Hui; Qiang, Jin Wei; Zhang, Guo Fu; Boyko, Orest B.; Wang, Shi Jia; Cai, Song Qi; Wang, Li
Abstract : Purpose: To investigate the spectrum of MRI appearances of ovarian serous borderline tumor (SBT). Materials and Methods: Following ethics approval, 31 patients with 51 histologically proven ovarian SBTs underwent preoperative MRI. Images were evaluated, by two observers for the location, shape, size, internal architecture, signal intensity, and extent or stage of the tumors. The MRI findings were correlated with pathological findings. Results: Twenty of 31 patients (65%) demonstrated bilateral ovarian SBTs on MRI. Three MRI morphological patterns of ovarian SBT were identified: (i) Mainly cystic mass with multiple intracystic papillary projections from the wall and septations was observed in 24 (47%) tumors. (ii) Solid mass with hierarchical branching papillary and fibrous stalk architecture was observed in 8 (16%) tumors. The branching papillary projections were hyperintensity on T2WI, intermediate intense on DWI, and enhanced intensely after the administration of Gd‐DTPA. The internal branching fibrous stalks were hypointensity on T2WI and enhanced slightly. (iii) Mixed cystic‐solid mass was observed in 19 (37%) tumors. The cystic and solid components had the architecture and signal intensity similar to those of cystic and solid SBTs. Papillary projections were the common architecture of all three types of tumors. Conclusion: On MRI, the ovarian SBT has some morphological distinguishing features. The solid papillary architecture with internal branching fibrous stalk is a somewhat more characteristic MRI appearance.J. Magn. Reson. Imaging 2014;40:151–156 . ©2013 Wiley Periodicals, Inc .